Handicraft Industry Development of Prerevolutionary Russia: An Investigation on Germanic Russianists of the Early 20th Century - Dorozhkin, Andrey G.; Koldomasov, Ilya O.; Drozdova, Tatiana V.; Velikanova, Svetlana S.; Kozhushkova, Natalia V.; Chernykh, Oksana P. (Journal of History Culture and Art Research, 2018)
Germanic Russian studies of the first third of the twentieth century had a certain interest in the development of handicraft industry in Russia at the turn of the 19-20th centuries. The researchers focused on the economic aspects of small-scale industry situation, some possible prospects of its further operation. Less attention was paid to social aspects, including the situation of direct producers. At the same time in the early twentieth century German experts in Russia did not deal directly with the functioning of the Russian non-censorship industry as a rule. This problem was analyzed in the work by A. Bargon, who was in Russian captivity during the First World War, and worked in the system of handicraft production in Russia for some time. However, it should be taken into account that the work by A.V. Bargon was published in 1933, in the conditions of the already emerging Nazi dictatorship, and the author was not a professional historian, or an economist. All this left an indelible imprint on his work, which is of a journalistic nature. It is of some source significance and interesting, on the one hand, as the eyewitness evidence of the Russian small industry position during the First World War, and on the other - as a product of Germanic Russian studies during the early-Nazi times. Therefore, a special attention was given to it, also due to the specialized focus of A.V. Bargon's work and the consonance of its assessments to the judgments of some historians from the second half of the 20th century.